The Malaysian Fund Managers Perspective on the Viability of Takaful Operators Investment - Amirul Afif Muhamat; Mohamad Nizam Jaafar; Norzitah Abdul Karim; Azreen Roslan; Mohd Faizal Basri (Universitas Negeri Surabaya, 2020)
Takaful operators are expected by the policyholders to act beyond the role of traditional insurance companies that only offer Shariah-compliant protection services. They are expected to be commercially viable. One of the ways to be commercially viable is takaful operators must be able to invest the policyholders' funds in the profitable investment avenues. Nevertheless, the critical issue before investing the funds is to develop products that are suitable with the takaful operators' investment strategy. This study employed a questionnaire survey to gather the feedback of fund managers from 11 takaful operators in Malaysia ” all were the senior staffs of takaful operators in Malaysia were surveyed. The questionnaire is developed in the form of a Likert scale ranging from 1 to 5 as the research instrument. By Delphi technique, the draft of the questionnaire was sent to a panel of experts for review, was adopted, and their feedback reflected in the final questionnaire. The experts were a shariah advisor, a corporate finance manager, and a senior executive at the central bank. Findings indicate that policyholders' expectations on their investments are met and the products so far compatible with takaful operators' investment strategies.